THE EFFECT OF CALCIUM HYDROXIDE PARTICLE SIZE ON DENTIN TUBULI HARDNESS - Atia Nurul Sidiqa; Pahargyan Arya Rajasa; Hartanto Endrowahyudi; Myrna Nurlatifah Zakaria (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Calcium hydroxide (Ca(OH)2) is an effective root canal treatment, with calcium and hydroxyl ions effectively released on day 7. However, prolonged use can diminish dentinal tubule hardness and dissolve the hydroxyapatite crystals within them. Nanoparticle Ca(OH)2 demonstrated superior antimicrobial activity compared to conventional Ca(OH)2 because of its deeper penetration into the dentinal tubules.. Purpose: This study aimed to evaluate the effect of particle size on dentinal tubule hardness. Methods: True experiment with fifteen premolars with one root canal, no caries, and apical closure were divided into three treatment groups: conventional Ca(OH)2 (group 1, n=5), Ca(OH)2 nanoparticles (group 2, n=5), and untreated (control group), n=5. All samples were incubated for 7 days, and hardness was measured using a micro-Vickers hardness tester at 1/3 of the root canal. Kruskal-Wallis test followed by Mann-whitney post hoc analysis was used to compare the mean microvickers hardness values among different groups. The level of significance was set at p<0.05. Results: The results showed that there was significant difference between conventional Ca(OH)2 (73.00 ± 2.71) and Ca(OH)2 nanoparticles (67.40 ± 0.62) p=0.01 and the control group (70.68 ± 1.70; p>0.05) and Ca(OH)2 nanoparticles p=0.03. Conclusions: The use of Ca(OH)2 nanoparticles as an intracanal medicament for 7 days reduced dentin microhardness, whereas conventional Ca(OH)2 did not result in any change in microhardness. Particle size affects the hardness of dentinal tubules.